Influence of social media towards customer purchase intention: case of Nissan Malaysia passenger vehicle / Siti Nurul Suraya Mohd Yusoff, Nor Emira Ismail and Norfaraliza Harun - Mohd Yusoff, Siti Nurul Suraya; Ismail, Nor Emira; Harun, Norfaraliza (Arshad Ayub Graduate Business School, 2018)
Social media usage has now become an important aspect of consumers' lives. For businesses, using the social media as one of the promotional methods has also become an important facet in their marketing strategies. However, the lack of using social media for some companies to attract customers to purchase their products require a more detailed study. This study is conducted to assess the influence of social media towards purchase intention of passenger vehicles among potential buyers which may be of importance to Tan Chong Motors Holding, the distributor of Nissan. The attitude, social norms, and perceived behavioral control of consumers who may have the intention to purchase cars may well influence their purchase intention and this may be relevant in the context of using social media platforms. Hence, by utilizing the online survey approach, this study was conducted on 152 respondents who were part time students in Arshad Ayub Graduate Business School (AAGBS). An interview was also carried out to identify the current situation within the company and to get relevant input for the SWOT analysis. The data obtained in this research was analyzed by using descriptive analysis, reliability analysis and regression analysis. The results concluded that attitude, social norms and perceived behavioral of using social media platforms have positive influence on the purchase intention of potential buyers. The recommended strategies include the investment on social media marketing to improve social media activities and improve customer service.